Concept Sphere of ‘Young Poland’ Free Verse Writing in Critical and Artistic Dimensions - Naumenko, Nataliia (My University, 2021)
The article gives a synesthetical analysis of several poems taken from ‘Young Poland’ (‘Młoda Polska’) period, considering its critical interpretations during the 20th – the beginning of the 21st cemtury. Studying Lesya’s survey of the ‘Young Poland’ poetry has conditioned the subject of this research, which is such insufficiently explored field as free verse writing. The nature of free verse would allow determining the specifications of generic and stylistic diffusion in works of a certain poet and observe formation of an individual vision of the world thereby reflected in re-interpreted initials of folklore verse. Taking impressionism, which is believed to be the common stylistic marker for ‘Young Poland’ lyrics, into consideration can evoke the researcher’s interest to vers libre as one of its characteristic phenomena. У статті з позицій синтезу мистецтв проаналізовано вільновіршову поезію періоду «Молодої Польщі» на тлі її критичних осмислень упродовж ХХ – початку ХХІ століть. Уважний погляд на формальні та змістові особливості молодопольської поезії зумовлює актуальність нашого дослідження – такий маловивчений аспект цього феномена, як вільне віршування. Природа верлібру дозволить визначити особливості взаємопроникнення жанрово-стильових рис у творчості певного автора і формуванні індивідуальної поетичної картини світу, заломлену крізь переосмислені фольклорні первини вільного вірша. Імпресіонізм, який, за свідченням переважної більшості науковців, є спільним стильовим знаменником лірики «Молодої Польщі», спонукає дослідника звернути увагу на верлібр як одне з його характерних явищ.
Keywords: кафедра іноземних мов професійного спрямування; віршування; верлібр; синтез мистецтв; образ; мотив; символ; критика; versification; free verse; artistic synthesis; image; motif; symbol; criticism